Bachelard-Flocon, Paysages. Il mouvement – Forza, Provocazione, Volontà tra éléments e poésie (Altre Modernità, 2012)
“Le graveur est voué au mouvement” writes Bachelard, commenting in the sign of movement, the fifteen tables of the engraver Albert Flocon, in a work composed by four hands in 1950, along the thin threshold that unites and separates art and philosophy, thematizing the movement – main principle for the psyche, imagination and dream – such as strength, creation and will. Particular thamatization, that if has amazing wealth of content, referring to the notions of  “will to power”, “creative imagination”, “provocation and promotion of materiality”, also acts as a bridge between two different formulations of the movement: on the one hand the elementalist movement, tied to air, water, earth and fire – Empedocle’s rizomata, as always, Aristotelian, beds as natural roots of natural feelings (this will be the case of Novalis, Poe, Nietzsche and Goethe, poets of air, water, fire, and earth, lords of the Tetravalent Doctrine of Poetic Temperaments); on the other hand a movement that, dropped from the material substrate, is a direct expression of the poetic word (this will be the case of flame or light in Novalis, or even the poetic du Phénix that cross, soaring, La Flamme d'une Chandelle or Fragments d'une Poétique du Feu). Complex process, which, engaging psyche, imagination and art at first on the elements (Material Imagination of the Elements) – passing through the psychologistic relief of Freud, Jung and Desoille – places the movement in the point of articulation between two different ontologies: the ontology of elements and the ontology of poetry.
Keywords: Engraving; Movement; Flocon; Creative imagination; Materiality; Ontology